2023
DOI: 10.1124/dmd.122.001009
|View full text |Cite
|
Sign up to set email alerts
|

Fifty Years of Aryl Hydrocarbon Receptor Research as Reflected in the Pages ofDrug Metabolism and Disposition

Abstract: The induction of multiple drug-metabolizing enzymes by halogenated and polycyclic aromatic hydrocarbon toxicants is mediated by the aryl hydrocarbons receptor (AHR). This fascinating receptor also has natural dietary and endogenous ligands, and much is now appreciated about the AHR's developmental and physiological roles, as well as its importance in cancer and other diseases. The past several years has witnessed increasing emphasis on understanding the multifaceted roles of the AHR in the immune system. Most … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 233 publications
0
8
0
Order By: Relevance
“…Extensive studies in the past two decades have identified many natural dietary and endogenous ligands of AhR and unmasked various physiological functions in normal development and homeostasis [144][145][146]. However, most AhR ligands are toxic xenobiotics, including halogenated aromatic hydrocarbons and polycyclic aromatic hydrocarbons [134,145]. In addition, AhR binds with several pharmaceuticals that are used clinically for multiple disorders [147].…”
Section: Aryl Hydrocarbon Receptormentioning
confidence: 99%
“…Extensive studies in the past two decades have identified many natural dietary and endogenous ligands of AhR and unmasked various physiological functions in normal development and homeostasis [144][145][146]. However, most AhR ligands are toxic xenobiotics, including halogenated aromatic hydrocarbons and polycyclic aromatic hydrocarbons [134,145]. In addition, AhR binds with several pharmaceuticals that are used clinically for multiple disorders [147].…”
Section: Aryl Hydrocarbon Receptormentioning
confidence: 99%
“…Members of the animal kingdom have grown distinctive protein sensors that enable them to acclimatize to the surrounding environment, such as the aryl hydrocarbon receptor (AhR). 1,2 AhR belongs to the basic helix−loop− helix(bHLH) PER-ARNT-SIM(PAS) family, which is composed of bHLH, PAS-A, PAS-B, and transactivation domains. 3−5 It is a ligand-activated transcription factor that integrates biological and metabolic inputs to control sophisticated cellular reactions, cell cycle regulations, and the immune system.…”
Section: Introductionmentioning
confidence: 99%
“…Members of the animal kingdom have grown distinctive protein sensors that enable them to acclimatize to the surrounding environment, such as the aryl hydrocarbon receptor (AhR). , AhR belongs to the basic helix–loop–helix­(bHLH) PER-ARNT-SIM­(PAS) family, which is composed of bHLH, PAS-A, PAS-B, and transactivation domains. It is a ligand-activated transcription factor that integrates biological and metabolic inputs to control sophisticated cellular reactions, cell cycle regulations, and the immune system. Upon activation, AhR regulates the expression of several genes, such as cytochrome P450 (CYP) family genes, including CYP1A1, CYP1A2, and CYP1B1, that contribute to xenobiotic metabolism-related functions. This ongoing stimulation of AhR by xenobiotics and environmental pollutants can lead to toxic consequences .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations